PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PADA PT BANK TABUNGAN PENSIUNAN NASIONAL TBK (BTPN) REGIONAL SUMATERA BAGIAN TENGAH - Firdawati, Kamaliah (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2014)
This empirical investigation aimed to determine the influence of the perceived presence of compensation and work environment toward job satisfaction and employee performance using samples from employers of PT Bank Tabungan Pensiunan Nasional, Tbk in Sumbagteng Area. Total of 161 questionnairs were given to selected employee and used for statistical analysis.Employee performance measures of some factors such as target reaches, operational standard, employee competences,working quantity and quality, workship between employees, creativityand consistences of employees. While for job satisfaction direct by satisfaction factor of the employees themselves to all facilities that given by the company include workingship between the employees in company environment. Compensation variable factor by salary, subsidy, insentive,bonus, health insurance, and availiability promotion chance. Work environment variable consist of factor such as comfortable placing of work, facilities, workship, and comunication. Analysis use Structural Equation Model (SEM) with result show that compensation and work environment have influence direct and indirect to job satisfaction and employee performance. This is evidenced with Critical Ratio (CR) value in above 2,00 and Parameter (P) value in under 0,05.